ANALISIS YURIDIS PUTUSAN NOMOR 787/PID.B/2021/PN STB TENTANG TINDAK PIDANA PENGANIAYAAN DENGAN DIRENCANAKAN LEBIH DAHULU - Stefani Megawati; Dian Adriawan dg. Tawang (Faculty of Law, Universitas Trisakti, 2023)
The crime of premeditated maltreatment is the act of a person who prepares a plan to maltreat another person by taking a machete to slash the victim, causing the victim to feel pain and suffer injuries. in decision Number 787/Pid.B/2021/PN Stb. The main issues raised are 1.) How is the act of the perpetrator of the crime of maltreatment with premeditation decided based on Article 351 Paragraph (1) of the Criminal Code, study of decision number 787/Pid B/2021/PN Stb); and 2.) What are the reasons for the judge in giving a decision based on Article 351 Paragraph (1) of the Criminal Code on the crime of maltreatment with premeditation, study of decision number 787/Pid B/2021/PN Stb)? This research uses a descriptive analysis type of normative research, using secondary data obtained from literature studies which are processed qualitatively by drawing research conclusions, namely 1.) The act of the perpetrator of the crime of maltreatment with premeditation decided by Article 351 Paragraph (1) of the Criminal Code is not in accordance with the defendant who violated Article 353 Paragraph (1) of the Criminal Code of maltreatment with premeditation; 2.) The reason for the judge to decide by using Article 351 Paragraph (1) of the Criminal Code on premeditated maltreatment is wrong and not in accordance with the purpose of punishment because he was only sentenced to two years and six months imprisonment.